(1-w)(4w-9)=0

Simple and best practice solution for (1-w)(4w-9)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (1-w)(4w-9)=0 equation:


Simplifying
(1 + -1w)(4w + -9) = 0

Reorder the terms:
(1 + -1w)(-9 + 4w) = 0

Multiply (1 + -1w) * (-9 + 4w)
(1(-9 + 4w) + -1w * (-9 + 4w)) = 0
((-9 * 1 + 4w * 1) + -1w * (-9 + 4w)) = 0
((-9 + 4w) + -1w * (-9 + 4w)) = 0
(-9 + 4w + (-9 * -1w + 4w * -1w)) = 0
(-9 + 4w + (9w + -4w2)) = 0

Combine like terms: 4w + 9w = 13w
(-9 + 13w + -4w2) = 0

Solving
-9 + 13w + -4w2 = 0

Solving for variable 'w'.

Factor a trinomial.
(-9 + 4w)(1 + -1w) = 0

Subproblem 1

Set the factor '(-9 + 4w)' equal to zero and attempt to solve: Simplifying -9 + 4w = 0 Solving -9 + 4w = 0 Move all terms containing w to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + 4w = 0 + 9 Combine like terms: -9 + 9 = 0 0 + 4w = 0 + 9 4w = 0 + 9 Combine like terms: 0 + 9 = 9 4w = 9 Divide each side by '4'. w = 2.25 Simplifying w = 2.25

Subproblem 2

Set the factor '(1 + -1w)' equal to zero and attempt to solve: Simplifying 1 + -1w = 0 Solving 1 + -1w = 0 Move all terms containing w to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1w = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1w = 0 + -1 -1w = 0 + -1 Combine like terms: 0 + -1 = -1 -1w = -1 Divide each side by '-1'. w = 1 Simplifying w = 1

Solution

w = {2.25, 1}

See similar equations:

| 15x^3+21x^2=0 | | 0=3+5x+x^2-x^3 | | 5.6=1.1x+1.2 | | 7tan^2x-7=0 | | Ln(x+7)=(3x-5) | | 6x+49=28x+9 | | 2(3x+4)+5x=-1 | | 9k-1=15 | | Ln(x+7)=ln(3x-5) | | (9y-2)(3y+5)= | | Log(7x)=3.5 | | E*-3x=7.1 | | 3t-4=4t+16 | | 3x+31=12x-559 | | 17y=3x-19 | | (9+9)=(8-8) | | 10x-63=11 | | 8x^2-9x+k=0 | | 7x-2x-3x+2.73=4.49 | | 3x-5=-41 | | 9p-7= | | z^2+56x-1920=0 | | 7x+12y=12 | | z/-4=11-5 | | 0.7x+0.5=0.9x-1.1 | | 5x-6y=19fory | | 6(3+4x)-8=202 | | 4z/10-1=-8 | | 28-4*X=8 | | 3(4-2n)=2(7-n) | | 0.5/6=120/x | | 5x=12+2y |

Equations solver categories